Pengembangan Media Pembelajaran Karakter Jujur dan Adil Integrasi Islam dan Budaya Lokal Berbasis Mobile Learning - Subair, Subair (Jurnal Didaktika Pendidikan Dasar, 2020)
The 21st Century demands that the transformation of the learning process of Islamic Religious Education and Human Rights become more interesting and inspiring. That is especially in instilling honest and fair character in students, one of which is through the development of more innovative learning media. This study aims to determine the initial conditions, design, feasibility, and effectiveness of the media developed at UPT SMP Negeri 2 Pinrang. The method used is Research and Development by adapting the 4D development model. The results showed that the initial conditions of learning at UPT SMP Negeri 2 Pinrang still relied on simple print and audio media. Next is the development of media whose content integrates Islamic values and local culture based on mobile learning. The results of the validation of media experts, material experts / learning practitioners, and students obtained results in the excellent category. The results of testing the effectiveness of the gain index showed significant results. It can be concluded that the media used is appropriate to be used in improving the quality of character learning for students.